2020
DOI: 10.21037/atm-20-3302
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of children with COVID-19: a rapid review and meta-analysis

Abstract: Background: Most guidelines on COVID-19 published so far include recommendations for patients regardless of age. Clinicians need a more accurate understanding of the clinical characteristics of children with COVID-19. Methods:We searched studies reporting clinical characteristics in children with COVID-19 published until March 31, 2020. We screened the literature, extracted the data and evaluated the risk of bias and quality of evidence of the included studies. We combined some of the outcomes (symptoms) in a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 75 publications
3
37
1
Order By: Relevance
“…Clinical manifestations of COVID-19 in children include fever, cough, shortness of breath, rhinorrhea, myalgia or fatigue, diarrhea, vomiting, and headache. Fever and cough have been consistently noted as the most common presenting symptoms in multiple studies across several countries [ 12 , 13 ]. In a meta-analysis of studies on the clinical characteristics of children with COVID-19, symptoms of fever and cough were present most commonly at 48% and 39%, respectively, while gastrointestinal symptoms such as vomiting and diarrhea were much less common at 7% and 6%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical manifestations of COVID-19 in children include fever, cough, shortness of breath, rhinorrhea, myalgia or fatigue, diarrhea, vomiting, and headache. Fever and cough have been consistently noted as the most common presenting symptoms in multiple studies across several countries [ 12 , 13 ]. In a meta-analysis of studies on the clinical characteristics of children with COVID-19, symptoms of fever and cough were present most commonly at 48% and 39%, respectively, while gastrointestinal symptoms such as vomiting and diarrhea were much less common at 7% and 6%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis of studies on the clinical characteristics of children with COVID-19, symptoms of fever and cough were present most commonly at 48% and 39%, respectively, while gastrointestinal symptoms such as vomiting and diarrhea were much less common at 7% and 6%, respectively. The majority of pediatric patients generally have mild symptoms [ 12 ]. Anosmia and ageusia are seldomly reported as presenting symptoms of COVID-19 in the pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…These papers did not describe clinical features, but only summarized laboratory findings. Wang et al [17] summarized the clinical characteristics and laboratory findings in children but it is difficult to apply these to all adults and correlation between the findings is not investigated. Lastly, Lovato et al [18], Fu et al [19] and Li et al [20] analyzed clinical characteristics and laboratory findings associated with critical outcomes such as intensive care unit (ICU) care or case-fatality rate (CFR).…”
Section: Summary Of Previously Published Meta-analysesmentioning
confidence: 99%
“…For this reason, most of the guidelines published so far are more appropriate for adults than for children. Several systematic reviews with simple meta-analysis have been reported, but these have mainly focused on the clinical characteristics of pediatric COVID-19 (5)(6)(7), and data on the transmissibility, rate of viral coinfections, and treatments of pediatric COVID-19 are still lacking. Asymptomatic transmission is the Achilles' heel of COVID-19 pandemic control, as reported by Gandhi et al (8), but the number of asymptomatic infections in children is unknown.…”
Section: Introductionmentioning
confidence: 99%